Advances and prospect in natural beauty evaluation: insights for the World Heritage karst - Xi Zhao; Kangning Xiong; Meng Zhang (Heritage Science)
Abstract Natural beauty evaluation is an important branch of geography and landscape studies and has profound impact on the protection and sustainable development of World Heritage sites (WHs). However, systematic literature reviews in this field are insufficient. In this study, we comprehensively analyzed 262 relevant studies in the Web of Science and CNKI databases published since 1982, systematically reviewed the research progress in the field of natural beauty evaluation, analyzed the current main research methods, theoretical frameworks, and application practices, and explored their specific implications for the World Heritage karst sites (WHKs). The following observations were made. (1) The number of publications has been increasing year by year, reaching its peak in 2019, indicating increasing research interest in this field. (2) The research content covers five aspects: theory, evaluation indicators, methods, technology, and World Heritage value. The proportion of research on technology integration (33.94%) and evaluation methods (28.05%) is the highest, accounting for 61.99% of the total, and indicating a positive inclination toward innovation and development of research methods. (3) Methodology tends toward interdisciplinary collaboration, and evaluation methods have gradually shifted from a single qualitative description to quantitative, diversified, and interdisciplinary comprehensive evaluation. The combination of traditional and emerging technologies such as SD method, SBE method, AHP method, neuroscience, and UGC data has increased, breaking through time and space constraints and expanding data sources. (4) In future studies, the assessment of natural beauty should concentrate on aesthetic preferences across diverse cultural contexts, develop a concept of global localization, and enhance evaluators' aesthetic perception through multisensory integration. Simultaneously utilizing UGC data to balance the authority of evaluation standards and the inclusiveness of evaluation systems, developing quantifiable indicators, and improving quantitative research in analogy methods; Finally, a karst landscape aesthetic evaluation model is constructed from both global and local perspectives, providing scientific reference for the formation of a unified evaluation system.